Wajan Bolic Sebagai Alat Penguat Signal Untuk Desa Minim Signal - Yulita Yulita; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Nurlinda Nurlinda; Andi Ilham Rivaldi (Unri Conference Series: Community Engagement, 2021)
Communication is an important element used to help realize common interests in achieving a goal to be achieved. Communication is very necessary in the continuity of the learning process, especially during this Covid-19 period. The Covid-19 pandemic has brought significant changes to various sectors, including the education sector, where all rely on the use of technology that can connect teachers and students, thus making it easy for students to get good network coverage to take part in online learning. This is a major problem for students who live in areas with minimal signal, where each student has to struggle to find a signal and even climb a hill which of course will be dangerous for his safety, as happened in Pationgi village, where the location is very far from the city, resulting in network coverage in the village is very minimal. The implementation of PKM will be a solution for the community in providing an alternative by converting used frying pans into simple signal amplifiers. This used skillet will be combined with a repeater equipped with unshielded twisted pair (UTP) cable so that the signal produced is much better and facilitates internet access through the empowerment of the youth of the Pationgi village mosque. The impact of implementing PKM supports the learning process during the Covid-19 pandemic, increases partner creativity and supports digital literacy programs.